Race and Sex across the French Atlantic : the Color of Black in Literary, Philosophical and Theater Discourse. - Ekotto, Frieda (Lexington Books, 2012)
Race and Sex across the French Atlantic is a critical reconceptualization of the contributions of France and the French-speaking world to race relations in the continental United States. Radically re-evaluating the work of French and Francophone cultural icons such as Jean Genet, Aime Cesaire, Frantz Fanon and Dany Laferriere, this book makes use of untapped historical archival records that link these writers to important African-American political activists and intellectuals such as Lorraine Hansberry, James Baldwin and the Black Panthers, and even to the white American writer Norman Mailer.